(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper presents the application of heuristic optimization techniques for determining optimal placement and sizing of photovoltaic-based distributed generation (PVDG) in a distribution system. Nowadays in all over world constant increasing request of electrical power is increasing. Mostly power demand is delivered by the standard power generating sources, but they because air pollution, global warming, degradation in fossil fuels and their increasing cost have made men to look towards renewable energy sources. The demand for more power along with interest in clean technique has driven one to develop distributed power generation systems using renewable energy sources. We should look for new power generation technologies. One answer which is recently in attention is micro grid system. Micro grid contains some natural energy sources. They may have solar cells, wind turbines, micro turbines, fuel cells and storage battery systems like fly-wheel, battery back-up. This paper proposed the improved gravitational search algorithm (IGSA) and its performances are compared with two other algorithms such as the gravitational search algorithm (GSA) and particle swarm optimization (PSO). A comparison of the performances is also made using optimization techniques when PVDGs are fixed at critical buses.